Enhancing Elementary Students' Character through Aswaja Values: The Contribution of Islamic Religious Education Teachers - Yusuf, Muhammad; Rahman, Kholilur; Hidayah, Fathi (JURNAL ISLAM NUSANTARA, 2024)
This study explores the role of Islamic Religious Education (PAI) teachers in fostering the values of Ahlus Sunnah wal Jamaah (Aswaja) to form a good and polite character in students at school. This is based on the need for character education amidst the strong influence of technology in the lives of elementary school students today. The research method used is a qualitative approach with a case study design involving direct observation, in-depth interviews, and documentation analysis in the school environment. Data analysis techniques include data reduction, data presentation, and conclusion drawing to process and analyze the collected data systematically. The results of the study show that the application of Aswaja values by PAI teachers has a positive impact on developing students' character, especially in terms of simplicity, patience, honesty, and empathy. The contribution of this research is to enrich the understanding of the strategic role of PAI teachers in supporting the formation of students' character, as well as provide recommendations for developing a value-based curriculum and better collaboration between schools, parents, and communities in supporting character education. This research implies the need for continuous teacher training and the integration of character education into the curriculum to address modern technological influences.